ANALYSIS OF THE REPORTING SYSTEM FOR ACCIDENTS AND OCCUPATIONAL DISEASES AMONG HOSPITAL NURSES IN INDONESIA: A CASE STUDY - Mawo, Florianus Hans Matheus; Arumdani, Intan Sekar; Khusna, Tachiyya Nailal (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: A person performing in a hospital can experience accidents and occupational diseases due to the high intensity of interaction with patients. The occurrence of occupational accidents is important to report, of course, it serves as recommendations for evaluation. This study was conducted at the Bajawa Regional General Hospital (RSUD Bajawa). Based on the results of the preliminary study, the number of work accidents occurred were 4 cases, but 2 cases were not reported in 2018. Purpose: This study aimed to analyze the constraints in reporting occupational accidents and occupational diseases at the Bajawa Regional General Hospital (RSUD Bajawa). Methods: the study design in this study used an intrinsic case study. Results: The results showed that there was a Standard Operating Procedure (SOP) and reporting flow for occupational accidents and occupational diseases at Bajawa Regional General Hospital (RSUD Bajawa), but not all nurses had the same understanding of the Standard Operating Procedure and reporting flow. There was a budget for Occupational Health and Safety activities, but it had not been allocated for recording and reporting activities. Reporting activities were still carried out only in verbal form. Conclusion: There is a need to socialize the SOP and reporting flow thoroughly to all nurses. Supporting facilities in the form of forms to record occupational accidents and diseases are not yet available in all rooms.